EFEKTIVITAS PEMUNGUTAN PAJAK BUMI DAN BANGUNAN DI DESA KAMANGA DUA KECAMATAN TOMPASO KABUPATEN MINAHASA - Mamesah, Frisinthia; PANGKEY, MASJE; KIYAI, BURHANUDDIN (JURNAL ADMINISTRASI PUBLIK, 2018)
This research aims to determine the effectiveness of land and building taxcollection in the village of Kamanga Dua, Tompaso Subdistrict. By applying thedescriptive-qualitative method, this research uses the types of primary and secondarydata, then the data is obtained using interview techniques and field observations. Afterand collected then analyzed using percentage analysis techniques to see the effectivenessof UN collection then interview data were also analyzed using interactive techniques.The results showed that: (1) Land and Building Tax Collection in Kamanga DuaVillage, Tompaso Subdistrict, Minahasa District was categorized in principle "Not yeteffective" or successful with an average achievement of 100 percent per year from thetarget set at 30,150 million rupiah on average per year. (2) The ineffectiveness of UNcollection in 2017 is caused by several things, including the transition of the UNmanagement from the central government to the district / city government so that taxofficials have not had time to effectively disseminate information to taxpayers and thereis an assumption that UN revenue is not fully utilized for the benefit of regionaldevelopment and even the impression of being misused by certain individuals. It isrecommended that in order to achieve the UN acceptance target in the village ofKamanga Dua, Tompaso Subdistrict, Minahasa District, the ability of UN collectionofficers who have adequate skills is needed, the government is advised to conduct specialtraining for UN collection officers. In order to optimize UN revenues so that they canachieve the set targets, the village government needs to disseminate information to themandatory UN whenever there are changes to the UN collection policy.Keywords: Effectiveness, Collection of Land and Building Taxes